Da-Homothetic Deformation of K-Contact Manifolds. (16th December 2013) - Nagaraja, H. G.; Premalatha, C. R.
Abstract : We study D a -homothetic deformations of K -contact manifolds. We prove that D a -homothetically deformed K -contact manifold is a generalized Sasakian space form if it is conharmonically flat. Further, we find expressions for scalar curvature of D a -homothetically deformed K -contact manifolds.